Error messages on learning Micro-CDS/ISIS the Philippine experience - Salang, Maria Maura C.; Cruz, Ma. Divina P.; Esquejo, Nemesio A. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1992)
The purpose of this study is to evaluate the user friendliness of Micro-CDS/ISIS focusing error messages. Specifically, it seeks to find out the error messages that are frequently encountered. It also determines how clearly the error messages are understood and examines if having computer/programming exposure facilitates learning the software. It ends by citing the problems encountered and difficulties experienced by the users and recommending possible solutions and suggestions.
The sample consisted of fifty Micro-CDS/ISIS users. The respondents are library/information personnel of the different libraries and information centers in Metro Manila. Frequencies and multiple regression are used for statistical tests. The major findings are : 1. There are six frequently encountered error messages which occur in data entry and data exchange. 2. A total of fifty-five error messages are unfamiliar to Micro-CDS/ISIS users. 3. Computer/programming experience and exposure of Micro-CDS/ISIS users has no effect on the occurrence of the problems and clarity of error messages on using the software. 4. The difficulties on learning Micro-CDS/ISIS by novice and experienced users are not the same.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: CDS/ISIS (Information retrieval system).